July 2024 - nutrition: rehydration, fluid balance, lactose-free milk - Dupont, Gregory (2024)
Interview with Luis Aragón-Vargas, first author of the paper (Aragon-Vargas et al (2024). Skimmed, Lactose-Free Milk Ingestion Postexercise: Rehydration Effectiveness and Gastrointestinal Disturbances Versus Water and a Sports Drink in Physically Active People. International Journal of Sport Nutrition and Exercise Metabolism.), who is affiliated at Human Movement Science Research Center (CIMOHU-UCR), University of Costa Rica (UCR), San Jose, Costa Rica. Dehydration during prolonged exercise presents challenges for athletic performance and overall health. Intense physical activity, especially in hot environments, leads to fluid and electrolyte loss, resulting in adverse effects like muscle fatigue, impaired cognitive function, and heat-related illnesses. Effective strategies for prompt fluid and electrolyte replenishment are essential for maintaining body homeostasis and supporting optimal recovery.